2005
DOI: 10.1021/ja0457718
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-Functionalized, 1.5-nm Gold Nanoparticles through Ligand Exchange Reactions:  Scope and Mechanism of Ligand Exchange

Abstract: Ligand exchange reactions of 1.5-nm triphenylphosphine-stabilized nanoparticles with omega-functionalized thiols provides a versatile approach to functionalized, 1.5-nm gold nanoparticles from a single precursor. We describe the broad scope of this method and the first mechanistic investigation of thiol-for-phosphine ligand exchanges. The method is convenient and practical and tolerates a surprisingly wide variety of technologically important functional groups while producing very stable nanoparticles that ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
426
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(440 citation statements)
references
References 53 publications
14
426
0
Order By: Relevance
“…Thiolated gold NPs, labelled as Au-SR exchange , were synthesized via ligand exchange reactions of phosphinestabilized NPs ͑Au-TPP͒ as previously described by Woehrle et al 26 The starting point was a solution of 0.156 g of Au-TPP in 40 ml of CH 2 Cl 2 , to this solution 0.156 g of dodecanethiol ͑Aldrich, 98.5%͒ were added. The resulting mixture was stirred at room temperature for 10 h to complete the ligand exchange reactions.…”
Section: A Np Synthesismentioning
confidence: 99%
“…Thiolated gold NPs, labelled as Au-SR exchange , were synthesized via ligand exchange reactions of phosphinestabilized NPs ͑Au-TPP͒ as previously described by Woehrle et al 26 The starting point was a solution of 0.156 g of Au-TPP in 40 ml of CH 2 Cl 2 , to this solution 0.156 g of dodecanethiol ͑Aldrich, 98.5%͒ were added. The resulting mixture was stirred at room temperature for 10 h to complete the ligand exchange reactions.…”
Section: A Np Synthesismentioning
confidence: 99%
“…Biocompatible coatings on nanoparticles that may protect proteins against direct and usually harmful interactions with the metal can be obtained by self-assembled monolayers (SAMs) of o-functionalised mercaptoalkanes. 3 Again, this method has been established for Au but, up to now, only one SERR spectroscopic study of proteins on SAM-coated AgNPs has been reported. 4 However, in that work rather unstable AgNP aggregates were used.…”
mentioning
confidence: 99%
“…The addition of TOAB affects the process of formation of mesoparticles in two ways: firstly, by lowering the rate of formation of Au atoms and, secondly, by adsorbing onto Au facets and promoting preferential crystalline growth. In the case of Type III and IV particles, in the first step of reduction of Au (III) an exchange of ligands takes place in the AuCl [18,19]. AuBr − 4 is a rather stable complex and consequently the reduction of Au(III) and the formation of gold atoms is slower in the presence of TOAB since the following reaction is more sluggish:…”
Section: Discussionmentioning
confidence: 99%